Crafting political gestures of locality: The transposition of artisanal traditions in the artwork of Catarina Branco. Issue 1 (1st March 2022) - Nolasco, Ana
This article seeks to shed light on the transposition of traditional crafts related to the popular religion of the Azores into the secular context of art in the works of Catarina Branco, taking two of the artist's exhibitions ‐ Fez-se Luz, 2012, and Alminhas, 2013 ‐ as case studies. The research first shows how this transposition leads to the cross-fertilization of the religious and artistic domains, imbuing art with greater spirituality and introducing reflections concerning contemporary issues, such as emigration and the position of women into the context of religion. Second, I discuss how the contingent nature of craft in art is used as a disruptive element that liberates the imagination, thought and feelings, dismantling hierarchies between the manual and the intellectual, the masculine and the feminine, as well as those between religion, art and craft, through embodied gesture. Religion is here understood in its wider sense as a form of mediation of the transcendent (Meyer 2009). I argue that these works can be seen as a political gesture, which highlights the past of women who lived in anonymity, simultaneously preserving and renewing traditional crafts that are dying out while also deconstructing the false dichotomy between the manual and the intellectual or spiritual. The act of papercutting gives physical form to the experiences of Azorean women, while at the same time addressing questions relevant to the human condition, including migration and the eternal search for transcendence. Through its inevitable polysemy, this act reveals meanings that have been hidden by habit, allowing the viewer to rediscover them.